A Comparison of Voluntary and Involuntary Child and Adolescent Inpatient Psychiatry Admissions. Issue 1 (2nd January 2016) - Persi, Joe; Bird, Brian M.; DeRoche, Christina
ABSTRACT: The study compares voluntary and involuntary groups of patients and provides the first detailed description of involuntary admissions to a Canadian child and adolescent inpatient psychiatry setting. The involuntary group was found to have a higher percentage of adolescents, patients with suicide risk, patients living away from families, and patients presenting outside of regular office hours. Involuntary patients were more likely to be provided with secure transportation to inpatient care than voluntary patients. No differences were found between groups in terms of gender, culture, problem severity, global functioning, or medication. Inpatient psychiatry assessed lower prevalence of suicide risk relative to referral sources, kept involuntary patients for shorter stays than voluntary patients, and rapidly terminated involuntary status for the majority. Based upon the study findings, it appears that involuntary referrals may provide reassuring admission after emergency department screening identifies possible severe risk of suicide. But, this reassurance may come at the cost of admitting a significant proportion of individuals without serious mental illness, and who may not require involuntary status or who may not go on to profit from inpatient care. Research is required to evaluate the determinants, costs, and benefits of involuntary admissions for patients and the mental health system.